Singlet molecular oxygen evolution upon simple acidification of aqueous hypochlorite: application to studies on the deleterious health effects of chlorinated drinking water. - Khan, A U (1994)
A study of the pH profile of the decomposition of aqueous hypochlorite has revealed the evolution (onset at pH 8) of single (1 delta g) molecular oxygen (singlet spin state dioxygen) detected spectroscopically (1268 nm), prior to the appearance of chlorine (onset at pH 5.5). The possible mechanism of the singlet state dioxygen evolution is presented, and the origin of its chloride ion dependence is discussed, especially in reference to chloride ion dependence of singlet molecular oxygen evolution in biological systems. Recent epidemiological analyses of the correlation of human cancer with chlorinated water supplies focus attention on the singlet oxygen mechanisms of DNA lesion formation.